Değişim ve kimlik bağlamında İstanbul'dan özgün bir mekânsal kesit: Rumelihisarı - (:unkn) unknown (My University, 2013)
Ait olduğu medeniyet ailesi, kültürel biçimlerinden anlaşılabilen kentler, orada yaşayan topluluğun estetik beğenilerini temsil eder. Kentin görünümleri; kentin mimari biçimlenmesinin yanı sıra doku, renk, koku, ses, rahatlık, konfor ve estetik haz duygusunu da içine alan ortam ve koşullar ile sarmalanır. Böylece her kent; kendi güzellik anlayışını, özgün havasını ve kimliğini kazanır. Bu çalışma, İstanbul şehir kültürünün özgün bir mekânsal kesitini oluşturan Rumelihisarı üzerinden, değişim ve kimlik bağlamında mahalle kültürünü ele almaktadır. Derinlemesine görüşme tekniği uygulanarak niteliksel bir alan araştırması yapılmış; ulaşılan veriler (1) aidiyet meselesi ve sosyal ayrışma, (2) doğayı kavrama ve yaşayış biçimleri, (3) komşuluk ilişkileri başlıkları altında açıklanmıştır. Son olarak, kimlik konusu tartışılmakta ve kent yönetimine yönelik öneriler geliştirilmektedir.

Through cultural forms of cities, one can find out the civilization family it belongs to, and this generally represents the value of the aesthetic tastes of the community living there. Views of the city are surrounded by an environment and conditions which not only contain architecture, but also textures, colors, smells, sounds, convenience, comfort, and a sense of aesthetic pleasure. So, each city has its own understanding of beauty, unique atmosphere, and identity. This study deals with the neighborhood culture within the context of change and identity based on Rumelihisarı, an authentic spatial cross-section of Istanbul s city culture. In-depth interviews were conducted through a qualitative technique, and data obtained from this study were analyzed with regards to (1) the question of belonging and social distinction, (2) the understanding of nature and lifestyles, and (3) neighborhood relations. Lastly, the identity of the city was discussed, and suggestions were developed for local administration.
A specific spatial cross-section from Istanbul in the context of change and ıdentity: Rumelihisarı
Keywords: Sosyoloji